Changes in the size structure of marine fish communities. (28th July 2017) - Bell, Richard J; Collie, Jeremy S; Branch, Trevor A; Fogarty, Michael J; Minto, Coilin; Ricard, Daniel
Abstract: Marine ecosystems have been heavily impacted by fishing pressure, which can cause major changes in the structure of communities. Fishing directly removes biomass and causes secondary effects such as changing predatory and competitive interactions and altering energy pathways, all of which affect the functional groups and size distributions of marine ecosystems. We conducted a meta-analysis of eighteen trawl surveys from around the world to identify if there have been consistent changes in size-structure and life history groups across ecosystems. Declining biomass trends for larger fish and invertebrates were present in nine systems, all in the North Atlantic, while seven ecosystems did not exhibit consistent declining trends in larger organisms. Two systems had alternative patterns. Smaller taxa, across all ecosystems, had biomass trends with time that were typically flat or slightly increasing. Changes in the ratio of pelagic taxa to demersal taxa were variable across the surveys. Pelagic species were not uniformly increasing, but did show periods of increase in certain regions. In the western Atlantic, the pelagic-to-demersal ratio increased across a number of surveys in the 1990s and declined in the mid 2000s. The trawl survey data suggest there have been considerable structural changes over time and region, but the patterns are not consistent across all ecosystems.